Socioeconomic Influence of Parents on Learning Achievement of PPKn Students of Class XI SMKS Ekatama Pekanbaru - Ira Desrawati; Jumili Arianto; Indra Primahardani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is motivated by a learning process that cannot be separated from the need for facilities and infrastructure. These needs will be fulfilled properly if the parents' economic situation is also good. With sufficient needs, it is hoped that the learning process can run smoothly, thus having an impact on learning achievement, one of which is ppkn. The purpose of this study was to determine the socioeconomic influence of parents on student learning achievement. The research was carried out at SMKS Ekatama Pekanbaru using the survey method. The results of the study were that there was a positive and significant socioeconomic influence of parents on the learning achievement of ppkn students of class XI SMKS Ekatama Pekanbaru by 19.2%. Then the f test obtained Fhitung of 7,109 and ftabel 4.17 which showed that Fhitung ≥ ftabel, so Ho was rejected and Ha was accepted which means that variable X affects variable Y.